Study of students' entrepreneurship interest as an indicator of opportunity for establishing business incubators in Lombok tourism polytechnic - Muh. Yahyaddin; Hamsu Hanafi; Christina Sianipar; Anak Agung Ngurah Sedana Putra; Mandra Mandra; Lalu Ahmad Zaki (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study had two goals: (1) to provide an overview of student entrepreneurship interest as an indicator of opportunities to establish a business incubator at the Lombok Tourism Polytechnic, and (2) to provide a contribution of thought and enrichment in the field of study and enrichment of the tourism business incubator as input and reference for future studies. (3) used as information and input for stakeholders in developing entrepreneurship. This study gathered primary data through a questionnaire distributed to 63 students from four different study programs. The data collection technique is purposive sampling, and the data analysis technique is descriptive responses. It was provided by respondents in the questionnaire. The results of this study indicate that: (1) flexibility, indicating the intention of respondents, 22% strongly agree (2) In terms of innovation, indicating the intention of respondents, 44% strongly agree. (3) social prestige, indicating the intention of respondents to engage in entrepreneurship. 48% strongly agree. (4) A personal challenge, indicating the intention of respondents 60% strongly agree. (5) Leadership, indicating the intention of respondents 45% of respondents agree on the benefits of leadership, indicating their intent. 51% strongly agree. (7) Being in charge, with 36% of respondents strongly agreeing.